Analysis of Deformation of Deep and Large Foundation Pit Support Structure and Impact on Neighbouring Buildings in Complex Environments - Chao Guo; Xiaodong Yang; Chengchao Guo; Pengfei Li (Buildings)
The development trend of urban underground space towards deep and large three-dimensional foundation pit projects in complex environments faces the challenges of deformation and instability of supporting structures, strong sensitivity of the surrounding environment, and significant limitations of the traditional design theory. Based on the ultra-long/deep foundation pit project at the Shenzhen Airport East Station, a refined three-dimensional finite element simulation is used to systematically study the deformation mechanism of the supporting structures of deep and large foundation pits under a complex environment and investigate the influence on the neighbouring buildings. In this study, a three-dimensional finite element model is constructed considering the soil–structure coupling effect, and the mechanical response law of the foundation pit under the compliant–inverse combination method is revealed. Based on ABAQUS 6.14, a 10 m wide strip-shaped model of the central island area and an environmental risk source model including an underground station and group pile foundation are established. The analysis shows the following: the lateral shift in the ground wall is distributed in a ‘convex belly’ shape, with a maximum displacement of 29.98 mm; the pit bottom is raised in the shape of the bottom of a rebutted pot, and the settlement behind the wall has an effect ranging up to 3.8 times the depth of the excavation; the lateral shift in the side wall of the neighbouring underground station and the differential settlement of the group piles validate the predictive ability of the model on the complex-environment coupling effect. The research results can provide guidance for the design and construction of support structure projects and similar projects.